Studi Etnomatematika: Eksplorasi Konsep Teorema Phytagoras pada Budaya Palembang (JURNAL PENELITIAN PENDIDIKAN MATEMATIKA, 2023)
Ethnomathematics is a study that combines mathematics and culture. Culture is a legacy passed down from ancestors that becomes a characteristic or characteristic of a particular region, one of the regions that has characteristics that are famous for its culture is the city of Palembang. Palembang city has various cultures that are in great demand by outsiders such as the Limas traditional house and jumputan cloth. Discussing about culture, this is certainly inseparable from learning concepts found in everyday life, one of which is the concept of learning mathematics. Where in this case the researcher takes the concept of mathematics on the phytagorean theorem associated with Limas houses and jumputan cloth. The type of research that researchers use is ethnographic qualitative research. Data sources are primary data and secondary data. Data collection techniques through interviews, observations and documentation. The data obtained was then analysed by data reduction, data presentation, and conclusions and verification. The result of this research is that Palembang culture, namely the Limas house roof, has the application of the phytagoras theorem concept. In the motifs of jumputan fabric patterns and the plan of the Limas house looking sideways contains the concept of proving the truth of the phytagoras theorem.